Support of turbocompressor unit equipment heat regime by heat insulation of gas-turbine engine - Кирилаш, Елена Ивановна; Костюк, Владимир Евгеньевич (Technology audit and production reserves, 2015)
Some problems of fire explosion safety and acceptable thermal state of power units of equipment of turbo-compressor units are considered. Thermal state of the power block equipment in the presence and in the absence of external thermal insulation of body of converted gas-turbine engine is investigated by the methods of aerodynamics. Thickness of the insulation mats placed on different parts of the engine body calculated on the basis of the surface temperature, that are maximum permissible under the terms of fire explosion safety. The results showed that the coating of the engine body by thermal insulation will significantly reduce the temperature of its outer surface and small-sized equipment of power unit with a small decrease in the efficiency of the turbine and engine power, because of the additional thermal expansion of the body. The usefulness of the external thermal insulation of bodies of converted engines working in the cover of power units of turbo-compressor units requires further feasibility study.